Pelatihan Internet Untuk Anak Yatim Dan Dhuafa Yayasan Amanatul Huda Tangerang Selatan - grace gata; Ratna Ujiandari; Atik Ariesta (Ikatan Ahli Informatika Indonesia, 2020)
One way to help orphans and underprivileged people to get the opportunity to learn the internet for increasing their horizons is through internet training that can improve their ability to use positive technology. Some of the problems faced include the lack of mastery of English, because most of the information on the internet is available in English, so there is need for training in searching the internet. The next problem is the control of internet users to distinguish good and bad information, so there is a need for debriefing in searching for information on the internet. This training activity aims to increase knowledge and skills in the field of computer applications and maximize the use of the internet, search with Google, create a personal blog for orphans Foundation of Amanatul Huda. At the end of the training, it was stated that participants expressed satisfaction with the training, the training material according to the needs of the participants was given a value of 94.7% from the results of the questionnaire distributed. Participants also stated that the material provided was complete and easily understood, this was stated at 93.3%.